Tractable Epidemiological Models for Economic Analysis - Martín Gonzalez-Eiras; Dirk Niepelt (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We contrast the canonical epidemiological SIR model due to Kermack and McKendrick (1927) with more tractable alternatives that offer similar degrees of “realism” and exibility. We provide results connecting the different models which can be exploited for calibration purposes. We use the expected spread of COVID-19 in the United States to exemplify our results.
Keywords: I18; 330; epidemiology; SIR model; logistic model; Covid-19